Sex‐specific role of alexithymia in associations between parental bonding and mental health: A moderated mediation model - Li Ru; Kajanoja Jani; Karlsson Linnea; Karlsson Hasse; Karukivi Max (Wiley, 2022)
Objective: This study aimed to explore the role of alexithymia and potential sex differences in the associations between perceived parental bonding and mental health.
Methods: The sample consists of 2421 parents from the FinnBrain Birth Cohort Study who completed the Parental Bonding Instrument (PBI), the Toronto Alexithymia Scale (TAS-20), the Edinburgh Postnatal Depression Scale (EPDS) and the anxiety subscale of the Symptom Checklist-90 (SCL-90). Moderated mediation analyses were conducted to examine possible mediating role of alexithymia and moderating role of sex in the associations between parental bonding and depressive/anxiety symptoms
Results: Alexithymia was found to be a potential mediator and sex be a moderator in the relations between perceived dysfunctional parental bonding and the psychological symptoms. Specifically, dysfunctional paternal bonding, especially paternal overprotection, had stronger indirect effects (via alexithymia) on the psychological symptoms in males.
Conclusions: This study indicates the importance of alexithymia in the parenting-related mental health impacts and highlights the significance of paternal bonding for the development of alexithymia and mental health problems in male populations. The findings improve the limited understanding of sex-related parental factors for alexithymia and mental health problems. Future studies in longitudinal designs are warranted to clarify the causal process of the mediation.